A organização do sistema de controle interno frente aos aspectos conceituais: o caso do município de Dilermando de Aguiar – RS - Nogueira, Ricardo da Rosa (2019)
This study deals with the subject of municipal internal control, specifically about the internal control practices adopted in Dilermando de Aguiar and the conceptual structure constituted, especially with respect to its theoretical and legal aspects. The discussions and analyzes are based on the information produced from the year 2012, when the guidelines to be observed in the structuring and operation of the municipal internal control systems have been regulated by the Court of Accounts of the State of Rio Grande do Sul. Despite having implemented the internal control system, the municipality was unable to translate this structure into administrative and operational improvements, as well as its fiscal and social indicators. Thus, the general objective of the work is to explain the structuring of the Municipal Internal Control System of Dilermando de Aguiar in relation to the theoretical structure and the legislation in force. In this perspective, the understanding of the functioning of the internal control system before the theoretical-legal framework can contribute to the control policies being carried out on a scientific basis. In order to meet the objective, the research strategy chosen was the case study, in a qualitative and exploratory way, using as theoretical framework the adapted use of the COSO I, Criteria of Control and Organizational Management Control System models. The information was collected from August 2018 to May 2019 through multiple sources of evidence such as interviews, documents, electronic databases and direct observation. The collection resulted in 8h: 30m of interviews, 822 documents, 25 direct observations and 42 databases verified. After the organization and treatment of the information, the findings were submitted to content analysis and resulted in six final categories: Organization of the Internal Control System; Fulfillment of Legal Purposes; Organizational Culture, Capacity and Purposes; Informational and Communication Systems; Environment, Activities and Monitoring of Control; and Risk Assessment. This categorization allowed the triangulation of information with current legislation and the theoretical models chosen. The results showed that the internal control practices of the unit studied are not organized in the form of a system and that the modeling of municipal internal control implies the innocuous attendance to theoretical and legal aspects. The main factors of the fragility of the internal control system of the case studied were: The design of the municipal internal control should be built from a primarily exogenous need of the Court of Accounts of the State of Rio Grande do Sul to the detriment of the endogenous structuring; organizational culture based on political and personal aspects; lack of evaluation, supervision and development of Internal Control; limitation of organizational capacity; deficiencies in information and communication systems; centralization of control in the Central Control Unit, precariousness in the control procedures and absence of risk assessment.